Aktifitas Fisik dan Status Gizi Siswa Kelas VIII dan IX di MTS Negeri 1 Murung - Dian Hafsari Fitri; Eko Kristanto Kunta Adjie (Pusat Riset dan Inovasi Nasional, 2023)
The problem of malnutrition status is a serious concern in children and teenagers because it affects their growth and development period. Nutritional status really affects physical development. Nutritional status is influenced by eating habits and daily physical activities. Lack of physical activity is increasing the chance of being overweight or obese. The aims of this research were to examine the correlation between physical activity and nutritional status of the students in VIII and IX grades at MTS Negeri 1 Murung. This research was conducted by using the observational method and cross sectional design. The research was conducted from July to December 2022 at MTS Negeri 1 Murung, in Central Borneo province. The sample of the research was 166 students. The results of the research showed that the majority of the students were in the IX grade (63.9%). Based on the age, the majority of students were 15 years old (63.9%). Based on gender, the majority of the students were females (68.1%). The physical activity of the students in VIII and IX grades at MTS Negeri 1 Murung was in the moderate category with 111 students (66.9%). The majority of nutritional status of the students in VIII and IX grades at MTS Negeri 1 Murung was in the normal category with 88 students (53%). There was a strong correlation between the physical activity and nutritional status of the students in the VIII and IX grades at MTS Negeri 1 Murung, the value of it was p=0.003.